Teknologi Tepat Guna Lampu Penerangan Energi Rendah Sebagai Awal Dasar Pembelajaran Sains Elektro-Fisika - Anwar Mujadin; Syachrial Putra Rifaldi (CV. Multi Kreasi Media, 2024)
Islamic boarding school students have more free time outside of class than in class with co-curricular activities that students must take part in as enrichment in extra-curricular activities. The Daar el-Qolam Islamic Boarding School is now equipped with skills education, agriculture, carpentry, scouting, arts and sports and skills development activities, especially in the fields of science and technology. The Daar el-Qolam Islamic boarding school has an excellent class (PEC) program. Robotics classes have become a trending extracurricular topic that attracts the attention of students. However, unfortunately, this robotics class is still difficult to implement for junior high school students because of programming problems. Through the Al Azhar University Electrical Engineering Study Program, odd semester 2023-2024, the learning of electro-physics science has been introduced as an initial stage before getting to know robotics (high technology) learning. From the results of the evaluation of the implementation of community service activities, the students have an enthusiastic interest in science because electro-physics science is easy to learn and implement, the students are eager for the community service implementation team to continue to conduct workshops with other science themes on a regular basis, even the students want to add to the science curriculum as an extra-curricular activity. seconded by a higher education institution. Implementation activities began by introducing appropriate technology for low energy lighting as a basic starting point for learning electro-physics science..